PERBEDAAN RERATA NILAI PCV ANTARA KELOMPOK PACKED RED CELL DARI TEKNIK PENGENDAPAN MANUAL DAN PACKED RED CELL DARI TEKNIK SENTRIFUGASI - Heru Setiawan; Intan Komalasari (Jurnal Fisioterapi dan Kesehatan Indonesia, 2021)
Packed Red Cell (PRC) components are the main therapy for hematological malignancies, thalassemia, and aplastic anemia. The PRC component was obtained by removing most of the plasma from the WB through a refrigerated centrifugation process. If there is no refrigerated centrifuge, this can be done by manual sedimentation at temperature 2-6oC for 12 hours or more. PRC components that have been made must meet predetermined quality standards, two of which are Hb concentration and PCV value. The purpose of this study was to see the significant differences in the value of PCV and Hb levels in PRC from the manual sedimentation technique for 25 hours with the centrifugation technique at a speed of 4000 gforce for 7 minutes. The design of this study is comparative analytic, which compares the results of PCV and Hb examinations on PRC from two different sedimentation techniques. Examination of PCV using the microhematocrit method and Hb using the photometer method with the Hemocue 301+ tool. The test results showed that the PCV value in manual sedimentation ranged from 57.50% to 75% with an average value of 66.42% and an SD value of 4.07, in the centrifugation technique it ranged from 56.50% to 74.0% with the average value is 65.72% and the SD value is 4.01. The Hb value in manual sedimentation PRC ranged from 17.55 g/dL to 25.30 g/dL with an average value of 21.39 and an SD value of 1.89, in the centrifugation technique it ranged from 17.10 g/dL to 25.40 g/dL with an average value of 21.19 g/dL and an SD value of 1.80. The statistical test was significantly different on the PCV value, the p value was 0.377 and the p value was 0.913 at the Hb concentration. The conclusion of this study is that there is no significant difference in the value of PCV and Hb levels in PRC from the manual sedimentation technique for 25 hours with the centrifugation technique. Generally, the value of PCV in PRC conforms to the standard, each as much as 70% in manual deposition and centrifugation. Likewise with the concentration of Hb, as much as 100% of PRC met the requirements for manual deposition and 96.7% met the standards for centrifugation sedimentation. This indicates that both sedimentation methods can be used..